Tinjauan Ekesegesis-Biblikal Terhadap 2 Timotius 3:15-16 Tentang Manfaat Pembelajaran Kitab Suci Dalam Membentuk Kepribadian dan Karakter Kristen - Benyamin, Yoel (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2022)
The teaching of the Word is very important in the life of a believer. By studying God's Word, the Bible becomes the standard for believers to live in God's righteousness. By making God's Word as a guide for living in God's truths. The Bible assures us of salvation in Jesus Christ. The Bible is the source of joy and comfort and the Bible is the source of true knowledge about God that makes humans grow up as it is ordained by God. So that in 2 Timothy 3: 15-16 it can become a standard of living for believers that when we know the Scriptures well we believers get wisdom. It is the benefits of studying God's word that give wisdom to those who do study it.AbstrakPengajaran Firman sangat penting dalam kehidupan orang percaya. Dengan pembelajaran akan Firman Tuhan, Alkitab menjadi tolak ukur orang percaya untuk hidup dalam kebenaran Allah. Dengan menjadikan Firman Tuhan sebagai pedoman untuk hidup dalam kebenaran-kebenaran Allah, Alkitab meyakinkan kita akan keselamatan di dalam Yesus Kristus. Alkitab adalah sumber sukacita dan penghiburan dan Alkitab adalah sebagai sumber pengetahuan yang benar tentang Allah yang membuat manusia bertumbuh dewasa sebagaimana difirmankan oleh Allah. Kitab 2Timotius 3:15-16 dapat menjadi suatu standar hidup orang percaya, dan dengan mengenal Kitab Suci dengan baik kita orang percaya memperoleh hikmat bagi orang-orang yang sungguh-sungguh mempelajarinya.